Pre-insolvency proceedings : a normative foundation and framework - Tollenaar, Nicolaes (Oxford : Oxford University Press, 2019)
This timely work evaluates the law regarding pre-insolvency proceedings, and in particular, the terms of the 2017 EU Directive. Setting the law in context, the text provides a conceptual framework for ideal practice, illustrating the implications of the new regime with specific practical examples.
This edition previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 14, 2019).
Keywords: Bankruptcy -- European Union countries